Economic Empowerment and Community Education through Bank Sampah: A Systematic Review of Waste Management Initiatives - Nurhayati, Sri; Taufikin, Taufikin; Susantrin, Siska; Noor, Agus Hasbi (Jurnal Ilmiah Profesi Pendidikan, 2025)
This article explores the contributions of Bank Sampah (Waste Bank) to economic empowerment and community participation in waste management, based on a systematic review of literature published between 2014 and 2024. The review highlights how Bank Sampah initiatives serve as effective tools for generating supplementary income for low-income households, promoting entrepreneurship, and fostering local economic development through waste recycling. In addition to their economic impact, Bank Sampah programs contribute significantly to community engagement by encouraging residents to take an active role in waste segregation and environmental stewardship. The review identifies the challenges that affect the sustainability of these programs, including financial dependency, infrastructure limitations, and cultural barriers. Despite these challenges, the Bank Sampah model has demonstrated considerable potential in enhancing social capital, empowering marginalized groups, and promoting environmental awareness. The findings underscore the need for policy support, robust community education, and strategic partnerships to ensure the long-term viability and scalability of Bank Sampah programs. This review provides valuable insights into how waste management initiatives can contribute to sustainable socio-economic development and environmental sustainability at the community level.